U.K. Hydrographic Department Experience in the use of Digitisers - Murt, G. E.; Adams, J. M. (The International Hydrographic Review, 2015)
Automated cartography was introduced into the U.K. Hydrographic Department about eight years ago when we installed a digitiser table and an automatic draughting system for office use, and automatic data logging and plotting systems on the three largest survey ships. Initially the emphasis within the office was on the mechanisation of the drawing of chart borders and navigation lattices. These are applications which require little data input but considerable computation, and most of the operation is therefore carried out by the machines. The application of automation to the drawing of irregular lines and scattered points involves the handling of very large amounts of data, and under present conditions most of these data are derived from documents. The equipment normally used for data input is the free cursor digitiser. This is a table on which the position of a cursor is sensed electrically and can be recorded onto paper or magnetic tape. The operator places the cursor on a point or traces it along a line, recording co-ordinates as required. Other information can be entered into the record by a keyboard. This manual data input is slow and prone to error, and the benefits of automation in this field are less clear-cut than in the production of computed linework such as borders and lattices.